Kościół apostolski o wyzwalaniu niewolników. Zarys problematyki - Szczur, Piotr (Vox Patrum, 2016)
The statements of St. Paul (1Cor 7:18-24; Gal 3:28; Phil 16-22) and Ignatius of Antioch (Epistula ad Polycarpum 4, 3) were analyzed in this paper. In these statements the authors wrote about the liberation of slaves. The advices of St. Paul and St. Ignatius were addressed to those slaves, who had become Christians. These advices come down to remind the slaves, that they should be obedient and subjected to their masters. However these advices were not said because of their approval of slavery as itself, but rather because they accepted the spiritual vision of Christian life, in which all people are brothers and children of God. The authors did not see the necessity of calling for liberation of slaves or demolition of slavery, because in their vision all people – sooner or later – come to abolish the yoke of slavery. It should be highlighted, that in social conditioning of those days, calling for the full abolition of slavery and for liberation of all slaves would be a revolution, which ruins the social order. However, the teaching of the authors of Ancient Church caused the gradual passing away from slavery, through creation the new relationship between master and his slave (i.e. John Chrysostom) and finally caused demolition of slavery.